The learning system of indigenous farming communities the case of T'boli farmers in Lake Sebu, South Cotabato, Philippines - Serrano, Evelie P. (2015)
This study described and analyzed how T'boli rice and corn farmers acquired and adopted farming knowledge. Qualitative data were gathers through key informant interviews, focus group discussion, and personal communications from T'boli farmers, extension workers, and community leaders in Lake Sebu, South Cotabato.
The learning system of the T'boli farmers follows an interactive and reflective process. Interacting with different sources of knowledge enables farmers to learn and adopt indigenous and modern farming practices. On the other hand, reflective learning enables them to merge indigenous and modern knowledge. These learning processes result to farming practices that are deemed useful, easy to use, practical, sustainable, appropriate, and/or culturally sensitive.
The farmers' ability to discern what is appropriate and useful for them shows their potential as partners in knowledge development and sharing as they are carriers of useful and adaptive knowledge. Hence, extension services in Lake Sebu can engage them as partners in knowledge development, and consequently, in the delivery of more appropriate extension interventions.
Keywords: T'boli (South Cotabato) -- Social life and customs; Indigenous knowledge, systems and practices; Agriculture -- T'boli (South Cotabato)